Acute Ingestion of a Mixed Flavonoid and Caffeine Supplement Increases Energy Expenditure and Fat Oxidation in Adult Women: A Randomized, Crossover Clinical Trial (OR29-07-19). (13th June 2019) - Nieman, David; Kohlmeier, Martin; Simonson, Andrew; Sha, Wei; Sakaguchi, Camila; Blevins, Tondra; Hattabaugh, Jaina
Abstract: Objectives: This randomized, double-blinded, crossover study measured the acute effect of ingesting a mixed flavonoid-caffeine (MFC) supplement compared to placebo (PL) on energy expenditure (EE) and fat oxidation (FATox ) in a metabolic chamber with pre-menopausal women (N = 19, mean ± SD, age 30.7 ± 8.0 y, BMI 25.7 ± 3.4 kg/m 2 ). Methods: The MFC supplement (678 mg flavonoids, split dose 8:30 am, 1:00 pm) contained quercetin (200 mg), green tea catechins (368 mg, 180 mg EGCG), and anthocyanins (128 mg) from bilberry extract, and 214 mg caffeine. Participants were measured twice in a metabolic chamber for a day, 4 weeks apart, with primary outcomes including EE for 5 defined time segments and 22 h (22hEE, 8:30–6:30 am), substrate utilization from the respiratory quotient (RQ), physical activity counts, and plasma caffeine levels (4:00 pm). Areas under the curve (AUC) for metabolic data from the MFC and PL trials were calculated for 5 time segments using the trapezoid rule, with a mixed linear model (GLM) used to evaluate the overall treatment effect, and paired t-tests used to compare data for each time segment. Results: EE and oxygen consumption for the MFC trial were significantly higher than PL (p < 0.001) when AUCs were compared as a whole and for each defined segment except during sleep. 22hEE with MFC was significantly higher than PL (1582 ± 143, 1535 ± 154 kcal/d, respectively, P = 0.003), with an average trial difference of 46.4 ± 57.8 kcal/d. Activity counts were not significantly different between trials (P = 0.671). RQ values were similar between the MFC and PL trials (0.819 ± 0.021, 0.826 ± 0.022, respectively, P = 0.281). FATox trended higher for MFC when evaluated using GLM (99.2 ± 14.0, 92.4 ± 14.4 grams/22 h, P = 0.054). Plasma caffeine levels were significantly higher in the MFC versus PL trial (5031 ± 289, 276 ± 323 ng/ml, respectively, P < 0.001). The trial differences for 22hEE and plasma caffeine were unrelated after controlling for age and body mass (r = −0.249, P = 0.139). Conclusions: EE was higher for MFC compared to PL, and similar to effects estimated from previous trials using caffeine alone. A small effect of the MFC on FATox was measured, in contrast to inconsistent findings previously reported for this caffeine dose. The trial variance for 22hEE was not related to the large variance in plasma caffeine levels. Funding Sources: Reoxcyn LLC.